Historical Character Design for a Mobile Game - Mustonen, Sanni; Paananen, Siiri; Colley, Ashley; Häkkilä, Jonna (Springer, 2022)
We present the design process for historical characters in a video game based on the local cultural history of the town Kemijärvi, Finland. The characters represented real people living in the town during the time period. Through an expert evaluation with 4 history experts, challenges in, e.g. authenticity, ethics, and narrative creation, were identified. The work provides insights to researchers and practitioners working on the development of games based around the topic of local history.